THE ECONOMIC ROLE OF WIVES IN ISLAMIC FAMILIES IN BALI: AN ANALYSIS OF AWIG-AWIG FROM THE PERSPECTIVE OF ASMA BARLAS (A STUDY IN BR. DINAS SAREN JAWA, BUDAKELING VILLAGE, KARANGASEM, BALI) - Mahrus Mahrus (Jurnal Ikhtibar Nusantara, 2026)
The issue of the dual role played by wives to support the family economy is very important, especially in the Balinese Islamic community in the midst of the dominance of patriarchal culture and customary rules (awig-awig). In the Br. Saren Jawa community in Budakeling Village, Karangasem Regency, Bali, Muslim wives contribute to working to meet the needs of their families, despite having to face negative prejudices and pressure from the social environment. This study aims to further explore the role of wives in helping the family economy among Balinese Islamic society and analyze this role using the perspective of gender thought Asma Barlas who emphasizes the importance of equality and opposes patriarchy.The method used in this study is qualitative with a phenomenological approach. Data was collected through observation, in-depth interviews, and documentation. The research subjects consist of Muslim wives who work and are active in supporting the family economy. This research also applies an empirical legal approach to explore the influence of customary awigs on the reality of the role of wives in the society.The findings of the study show that the role of wives is not only limited to the domestic sphere, but also reaches the public sector both formally and informally. From Asma Barlas' point of view, the involvement of wives in work is a form of resistance to the patriarchal system that limits women's freedom. The involvement of Muslim wives in Bali is more than just meeting economic needs, but also part of efforts to liberate gender roles. This study concludes that the dual role of wives in Islamic society in Bali reflects social power and change within the framework of balanced Islamic values..